Investigation of Minkowski Patch Antenna with Meander Line Split Ring Resonator (ML-SRR) Structure - Hassan, Nornikman; Ahmad, B. H.; Abd Aziz, M. Z. A.; Rahim, M. K. A.; Othman, A. R. (2013)
Abstract—The objective of this paper is to investigate the effect of the meander line split ring resonator on the modified Minkowski patch antenna. In this work, a modified Minkowski patch antenna with meander line split ring resonator (ML-SRR)and quadruple-P shaped split ring resonator (QPS-SRR)structure is presented. This proposed modified patch antenna with SRRs structures achieved remarkable 2.644 dB of gain at the frequency of 2.402 GHz compared to the normal Minkowski antenna without SRR structures with only 2.348 dB. This antenna had been simulated in the CST Microwave Studio simulation software.